Analysis of observed performance of a deep excavation straddled by shallowly buried pressurized pipelines and underneath traversed by planned tunnels. (February 2023) - Guo, Panpan; Gong, Xiaonan; Wang, Yixian; Lin, Hang; Zhao, Yanlin
Highlights: Field observations of a deep braced excavation interrupted directly by buried pipelines and planned tunnels are presented. Observed performance of ground, groundwater, excavation support structures, and pipelines are interpreted and discussed. Existing empirical envelops for relationships between observed performance and relevant parameters are verified. Abstract: The objective of this paper is to analyze the observed performance of a deep excavation facing severe restrictions from underground facilities or structures in Suzhou, China. The first source of the restrictions comes from two shallowly buried pressurized pipelines that straddle the excavation at an intersection angle of about 81°. The pipelines need to be well protected at the site during the construction to ensure the normal life of the local resident. The second source of the restrictions arises from the twin tunnels that are planned to be constructed beneath the excavation in the future for Suzhou Metro Line 14. The planned tunnels will be constructed using a tunnel boring machine, which necessitates the reservation of favorable conditions by the present excavation project. Because of these restrictions, the form of the excavation support system becomes complicated, and the performance of the excavation will inevitably differ from that of the common excavations. Based on a thorough analysis of the extensive field performance data collected by means of settlement points and inclinometers located within and adjacent to the excavation, the characteristics of the ground surface settlements, lateral ground movements, ground water table variations, vertical and lateral displacements atop diaphragm walls, vertical displacements atop lattice column, axial forces in concrete strut, and vertical and lateral pipeline deformations are captured. Despite the discontinuity of the peripheral retaining wall and the shortened wall height on the discontinuous sides, the ground and structural deformations are well controlled by the specially designed excavation support system. The pipelines are slightly uplifted by the suspension system, with the maximum vertical pipeline displacement being lower by an order of magnitude than the commonly observed maximum pipeline settlements in the literature. The existing empirical envelops are found to be site-specific in applicability, and are recommended to incorporate the field observations of this unusual deep braced excavation case history.